2010
DOI: 10.1159/000322364
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Bevacizumab and Cytokine Levels in Major and Macular Branch Retinal Vein Occlusion

Abstract: Purpose: My aim was to evaluate the effect of intravitreal bevacizumab and to determine the concentrations of inflammatory cytokines in patients with macular edema due to branch retinal vein occlusion (BRVO), according to the site of the occlusion. Methods: In a prospective interventional case series, 46 eyes of patients with macular edema due to major (n = 30) or macular BRVO (n = 16) were included. The patients were treated primarily with intravitreal bevacizumab (1.25 mg/0.05 ml) and completed 12 months of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 36 publications
2
22
0
1
Order By: Relevance
“…These findings are in agreement with the report by Lim [5], and may be related to the difference in the extent of retinal involvement between the two groups. We also found that the aqueous humor levels of sVEGFR-1 and PlGF were significantly higher in the major BRVO group than in the macular BRVO group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are in agreement with the report by Lim [5], and may be related to the difference in the extent of retinal involvement between the two groups. We also found that the aqueous humor levels of sVEGFR-1 and PlGF were significantly higher in the major BRVO group than in the macular BRVO group.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, macular BRVO is unlikely to be associated with neovascularization because a smaller area of the retina is affected, but macular edema and visual impairment develop frequently [4]. Lim [5] reported that treatment of macular BRVO required fewer doses of intravitreal bevacizumab than major BRVO and was associated with a lower level of vascular endothelial growth factor (VEGF) in the aqueous humor. We have also reported that the level of VEGF in the vitreous fluid was lower in macular BRVO than in major BRVO [6].…”
Section: Introductionmentioning
confidence: 99%
“…We also noted that the differences between the drugs in BCVA and CMT changes were more prominent in the ischemic type of BRVO. It has been shown that VEGF is a key factor for macular edema in retinal vein occlusion [20,21], Therefore, inhibition of VEGF should theoretically offer a therapeutic benefit for BRVO. This effect has been shown with anti-VEGF drugs such as bevacizumab [8][9][10][11][12][22][23][24], ranibizumab [25,26], and pegaptanib [27] in terms of both VA improvement and CMT reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular damage due to extension of the zone affected by venous occlusion is accompanied by complex cellular changes and an inflammatory response. Lim et al reported that macular BRVO required less treatment and was associated with lower levels of inflammatory factors in the aqueous humor than major BRVO [5]. However, little is known about the influence on inflammatory factors in the vitreous fluid of the site of occlusion causing BRVO.…”
Section: Introductionmentioning
confidence: 99%